Association between Knowledge, Preventive Attitudes, and HIV/AIDS Preventive Behaviors Among High School Students - Dolfinus Yufu Bouway; Fathu Rahmah Azizah; Inriyanti Assa; Katarina Lodia Tuturop; Agustina Regina Yufuai (MEDICA (International Medical Scientific Journal), 2026)
HIV/AIDS remains a major global health problem, particularly among adolescents who are vulnerable to risky behaviors. This study aimed to analyze the association between HIV/AIDS knowledge, preventive attitudes, and HIV/AIDS preventive behaviors among high school students in Jayapura City. A quantitative cross-sectional design was conducted in 17 high schools in Jayapura City from September to October 2025 involving 540 students selected as respondents. Data were collected using a structured questionnaire distributed through Google Forms and analyzed using descriptive statistics and Spearman Rank correlation test with a significance level of p < 0.05. The results showed that most respondents had good HIV/AIDS knowledge (85.6%) and positive preventive attitudes (78.9%), while 65.2% demonstrated good prevention efforts. The Spearman Rank test indicated a significant but weak positive relationship between HIV/AIDS knowledge and prevention efforts (r = 0.230; p = 0.000), and a moderate positive relationship between preventive attitudes and prevention efforts (r = 0.403; p = 0.000). In conclusion, both HIV/AIDS knowledge and preventive attitudes are significantly associated with prevention efforts among high school students in Jayapura City, with preventive attitudes showing a stronger relationship than knowledge, and strengthening school-based HIV/AIDS education programs is recommended to improve adolescent preventive behaviors. This study is limited by its cross-sectional design, which precludes causal inference, and its reliance on self-reported data, which may be subject to social desirability bias.